Implementasi Nilai Kebangsaan Untuk Meningkatkan Cybersecurity: Berbasis UUD 1945: Studi Kasus Pada Perusahaan Valve Corporation Pada Aplikasi Steam - Matthew Greenly Tamima; Edy Soesanto; Muhammad Moreno Alkhafidz (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In today's digital age, cybersecurity resilience is an urgent need. Organizations around the world face increasingly complex and rapidly changing threats. Given these challenges, it can damage national values. Risk-based security management has emerged as an effective way to improve cybersecurity resilience. The purpose of this study is to investigate how the implementation of risk-based security controls can improve cybersecurity resilience in the Company's environment based on the perspective of the 1945 Constitution.This study employs content analysis method to investigate policies, security practices, and incidents that occur at Valve Corporation in the context of cyber security. The research findings indicate that Valve Corporation has adopted various security strategies and technologies to protect their data and infrastructure from cyberattacks. However, there are still challenges such as evolving security threats and the complexity of global networks that require continuous updates in their security strategies.From the perspective of the 1945 Constitution, cyber security at Valve Corporation is also related to the protection of individual rights, information openness, and national technological independence. Therefore, companies need to consider national values in designing their security policies to ensure effective data protection while complying with relevant regulations.This research makes a valuable contribution to the understanding of the importance of risk-based security management in improving cyber security resilience, as well as providing practical guidance for organizations looking to improve their security strategies based on nationality values in the face of evolving threats in the digital world.